Smart Security System for Housing Using Website-Based MQTT - Tobing, Nindi Karynnina Luban; Rakhmania, Amalia Eka; Rasyid, Abdul (Jurnal Jaringan Telekomunikasi, 2024)
The housing security system is one of the aspects of implementing a security system in several house buildings which have several functions that work to secure assets in the building. Then in residential areas it is difficult to carry out intense security. This study designed a "Smart Security System in Housing Using Website-Based MQTT". This system is equipped with PIR sensors, LDR, ACS 712, and limit switches that are placed in each house. PIR sensors are used to detect human movement, limit switches are used to detect open doors, and LDR sensors are used to automate outside lights when homeowners activate outdoor mode. The ACS 712 sensor functions to give a warning of an anomaly in current usage. Using ESP8266 as a controller that sends data to the online MQTT broker "broker.mqtt-dashboard.com" which is equipped with the cloud. Home owners website programming using Node-RED installed on Raspi. Likewise with the security guard website using Node-RED as a website design. In monitoring at the security guard, you can monitor the security of the doors in each house. The results of the accuracy of the PIR sensor are only able to detect movement at a distance of less than 400 cm. The LDR sensor used in outdoor lighting automation with a voltage limit value above 2.56 V detects no light intensity. The accuracy of the ACS 712 current sensor in house 1 is 95% and house 2 is 94%.